First Report of a Nematode Pterygodermatites affinis Parasitizing a Stray Cat (Felis catus) from North India - Kumar, Pradeep; Tiwari, Jitendra; Kumar Singh, Alok; Kishor Tiwari, Vinay; Kamal, Tarun (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The genus Pterygodermatites (Order: Spirurida, Family:  Rictulariidae) represents a group of spirurid nematodes  known for their complex life cycles and wide host range  among terrestrial vertebrates. These nematodes are primarily  intestinal parasites of small mammals, with the majority of  species infecting rodents and insectivores (Anderson et al.,  2009). Occasional infestations have also been reported in  carnivorous hosts, including wild canids and felids, although  such occurrences remain relatively rare. Transmission of  Pterygodermatites spp. follows an indirect life cycle involving  arthropod intermediate hosts typically cockroaches or  beetles which ingest embryonated eggs and in turn are  consumed by the definitive mammalian host (Yue et al., 1986;  Sundar et al., 2023). While the genus has a cosmopolitan  distribution, most documented infections in felids are  restricted to regions in Europe and North Africa (Feliu et al.,  1997). In felines, infections are often under-diagnosed due  to the cryptic nature of parasitism, limited veterinary care for  stray animals, and a general lack of targeted parasitological  surveillance. Stray cats, in particular, occupy a unique  ecological niche. Often unmanaged and lacking routine  veterinary attention, they serve as potential reservoirs and  transmission agents for a variety of helminth parasites, some  of which may pose risks to human and animal health (Alho  et al., 2017; Khedri et al., 2024). In India, while several studies have documented the  presence of gastrointestinal helminths in stray cats, infections  with Pterygodermatites spp. have remained unreported. The  absence of previous records may be attributed to limited  diagnostic resolution, lack of comprehensive morphological  examinations, or true absence of this nematode in local cat  populations. The present study fills this gap by documenting,  for the first time, the presence of Pterygodermatites affinis in  a stray domestic cat (Felis catus) from Mathura, a semi-urban  region in northern India characterized by a high density of  free-roaming animals and poor waste management. This  report contributes new data to the parasitological record,  extending both the host range and geographical distribution  of P. affinis, and highlights the urgent need for integrated,  One Health-based parasitic surveillance in urban and peri urban environments.
Keywords: Felis catus; Nematode; Pterygodermatites affinis; Spirurida; Zoonotic